Manganese superoxide dismutase is dispensable for post-natal development and lactation in the murine mammary gland - Case, Adam J. (2012)
Mammary gland development is a multistage process requiring tightly regulated spatial and temporal signalling pathways. Many of these pathways have been shown to be sensitive to oxidative stress. Understanding that the loss of manganese superoxide dismutase (Sod2) leads to increased cellular oxidative stress, and that the loss or silencing of this enzyme has been implicated in numerous pathologies including those of the mammary gland, we sought to examine the role of Sod2 in mammary gland development and function in situ in the mouse mammary gland. Using Cre-recombination driven by the mouse mammary tumor virus (MMTV) promoter, we created a mammary-specific post-natal conditional Sod2 knock-out mouse model. Surprisingly, while substantial decreases in Sod2 were noted throughout both virgin and lactating adult mammary glands, no significant changes in developmental structures either pre- or post-pregnancy were observed histologically. Moreover, mothers lacking mammary gland expression of Sod2 were able to sustain equal numbers of litters, equal pups per litter, and equal pup weights as were control animals. Overall, our results demonstrate that loss of Sod2 expression is not universally toxic to all cell types and that excess mitochondrial superoxide can apparently be tolerated during the development and function of post-natal mammary glands.